Analyse der Verletzungsproblematik im Skisprung - Goertzen, M.; Nalbach, N.; Gürtler, R. (Deutsche Zeitschrift für Sportmedizin, 2001)
Purpose of study: Due to the fact that few data are available in the medical literature on nordic ski jumping injuries, we performed a prospective study on types and frequencies of injuries in nordic ski jumpers. Material and methods: 52 international world-cup participants and 61 elite Austrian junior athletes were examined over a 2-year period (1996-1998). The mean age of the world class athletes was 20.6 yrs., the mean age of the eltite junior athletes was 15.6 yrs. Injury questionnaires were used to evaluate specific details on the types, circumstances, and outcomes of their injuries. Results: 81.1 % of all injuries occurred during non-sports specific training activities. Only 18.9 % of injuries are directly related to falls on the hills. Typical overuse problems were low back pain and anterior knee pain. The most frequent acute injuries were thigh muscle strains, fibular ligament ruptures and shoulder or clavicula fractures. The mean training duration in world cup athletes was 34.1 hours/week, in junior atheletes 20.6 hours/week. World cup jumpers averaged 996 jumps, junior athletes 876 jumps/year. The fall rate per 1000 jumps was significantly higher in juniors (6.39 falls/1000 jumps) than in world class athletes (4.24 falls/1000 jumps). The injury rate for juniors and for world cup jumpers was 0.41 and 0.23 injuries per 1000 jumps, respectively. Higher injury rates were seen on winter than on summer mattress slopes. Discussion: Ski jumping injuries due to falls are strongly related to two factors: technical faults and ramp grooming, which is determined by weather and hill maintenance. In conclusion, we find that the injury rate in ski jumpers has been greatly overestimated by the public. The injury rate is less than that reported for most other olympic sport disciplines. The results of our survey show that there is still room for improvement in safety.